Seasonality of Biennial Burning Has No Adverse Effects on Mature Longleaf Pine Survival or Productivity - Willis, John L.; Sharma, Ajay; Kush, John S. (Frontiers in Forests and Global Change, 2021)
Emulating natural disturbance has become an increasingly important restoration strategy. In the fire-maintained woodlands of the southeastern United States, contemporary restoration efforts have focused on approximating the historical fire regime by burning at short intervals. Due to concerns over escape and damage to mature trees, most prescribed burning has occurred in the dormant season, which is inconsistent with the historical prevalence of lightning-initiated fire in the region. This discordance between contemporary prescribed burning and what is thought to be the historical fire regime has led some to question whether dormant season burning should remain the most common management practice; however, little is known about the long-term effects of repeated growing season burning on the health and productivity of desirable tree species. To address this question, we report on a long-term experiment comparing the effects of seasonal biennial burning (winter, spring, summer) and no burning on the final survival status, height, diameter, and volume growth of 892 mature longleaf pine (Pinus palustris) over 23 years in three mature even-aged stands in southern Alabama, USA. Overall, longleaf pine survival across all treatments averaged 81 ± 2 % [s.e]. Among seasonal burn treatments, survival was highest in the spring burns (82 ± 4 %) but did not vary significantly from any other treatment (summer - 79 ± 4 %, winter - 81 ± 4 %, unburned - 84 ± 4 %). However, survival was statistically influenced by initial diameter at breast height, as survival of trees in the largest size class (30 cm) was 40 % higher than trees in the smallest size class (5 cm). Productivity of longleaf pine was not significantly different among treatment averages in terms of volume (38.9 - 44.1 ± 6.0 m3ha-1), diameter (6.0 - 6.7 ± 0.3 cm), and height (2.5 – 3.4 ± 0.4 m). Collectively, our results demonstrate that burning outside the dormant season will have little impact on mature longleaf pine survival and growth. This finding has important implications for the maintenance of restored southeastern woodlands, as interest in burning outside the dormant season continues to grow.